Pengaruh Financial Literacy &Financial Technology Terhadap Business Sustainability: Studi Kasus pada UMKM di Kabupaten Karawang - Yanti; Lilis Lasmini; Izqa Khikma Mufrodah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to examine the influence of financial literacy and financial technology on the business sustainability of micro, small and medium enterprises (MSMEs). The population in this study is MSME actors in Karawang Regency. The technique used is quantitative descriptive, the primary data collection used is by distributing an online questionnaire to 119 participants using the purposive sampling method. The data analysis used is a multiple regression analysis technique with a test tool using PLS 3.0. The results of this study show that there is an influence of financial technology on business sustainability, but it has not been balanced with knowledge about financial literacy. The researcher hopes that MSME actors will increase their knowledge of good financial literacy so that they can make appropriate management and financial decisions to realize business sustainability.